IRON ISOTOPE FRACTIONATION DURING MICROBIAL REDUCTION OF IRON: THE IMPORTANCE OF ADSORPTION - Icopini G.A.; Brantley S.L.; Anbar A.D.; Ruebush S.S.; Tien M. (My University, 2004)
In experiments investigating the causes of Fe isotope fractionation, the d56/54Fe value of Fe(II) remaining in solution (Fe(II)(aq)) after reduction of Fe(III) (goethite) by Shewanella putrefaciens is ;21.2‰ relative to the goethite, in agreement with previous research. The addition of an electron shuttle did not affect fractionation, suggesting that Fe isotope fractionation may not be related to the kinetics of the electron transfer. Furthermore, in abiotic, anaerobic FeCl2(aq) experiments in which approximately one-third of Fe(II)(aq) is lost from solution due to adsorption of Fe(II) onto goethite, the d56/54Fe value of Fe(II)(aq) remaining in solution is shifted by 20.8‰ relative to FeCl 2. This finding demonstrates that anaerobic nonbiological interaction between Fe(II) and goethite can generate signif- icant Fe isotope fractionation. Acid extraction of sorbed Fe(II) from goethite in experi- ments reveals that heavy Fe preferentially sorbs to goethite. Simple mass-balance modeling indicates that the isotopic composition of the sorbed Fe(II) pool is ;11.5‰ to 12.5‰ heavier than Fe in the goethite (;2.7‰-3.7‰ heavier than aqueous Fe(II)). Mass balance is also consistent with a pool of heavy Fe that is not released to solution during acid extraction.